2020
DOI: 10.5114/ceh.2020.102155
|View full text |Cite
|
Sign up to set email alerts
|

Physician awareness of hepatitis C virus among different departments

Abstract: Aim of the study:To determine the anti-hepatitis C virus (HCV) positivity in our region and to evaluate physician awareness of HCV among different inpatient and outpatient departments in a tertiary reference center in Turkey. Material and methods: This retrospective study was conducted between January 2017 and January 2020. The patients tested for anti-HCV for any reason were enrolled from the data of all patients admitted to our hospital, which is the reference center of the region. Results: A total of 121,49… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…The highest anti-HCV positivity rate was found in patients over 50 years of age [8,11]. Similarly, we found that the mean age of the patients was 63 years in our study.…”
Section: Discussionsupporting
confidence: 81%
“…The highest anti-HCV positivity rate was found in patients over 50 years of age [8,11]. Similarly, we found that the mean age of the patients was 63 years in our study.…”
Section: Discussionsupporting
confidence: 81%
“…A general lack of HCV awareness, low sense of perceived risk and fear of stigma may have accounted for the low uptake 29,33,34 . Service provider barriers may have also contributed to these low rates as a lack of HCV awareness, and low self‐efficacy in HCV testing reportedly deter physicians from offering HCV‐testing and treatment services to their patients 12,35 . Therefore, routine physician training on HCV screening and testing with more targeted public HCV‐specific education is needed to improve HCV testing uptake and facilitate the integration of routine HCV screening into primary care consultation in China.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, only 58.5% of patients with positive HCV RNA at HCC diagnosis received DAA treatment in this study, further highlighting the severely suboptimal treatment rate even among patients with confirmed viraemic HCV‐related HCC 18,19 . As such, the low treatment rate demonstrates the need for continual education among practitioners and the public about the need to screen for HCV as well as the availability of potentially curative treatment with relatively mild side effects 20–26 . In this light, according to the U.S. Preventive Task Force, all U.S. adults should be screened for HCV at least once in their lifetime 27 .…”
Section: Discussionmentioning
confidence: 87%
“…18,19 As such, the low treatment rate demonstrates the need for continual education among practitioners and the public about the need to screen for HCV as well as the availability of potentially curative treatment with relatively mild side effects. [20][21][22][23][24][25][26] In this light, according to the U.S. Preventive Task Force, all U.S. adults should be screened for HCV at least once in their lifetime. 27 Furthermore, surveillance for HCC needs to be encouraged among those with cirrhosis to preclude the diagnosis of advanced HCC.…”
Section: Discussionmentioning
confidence: 99%